'The Fools Argue about Flesh and Meat': Sikhs and Vegetarianism. (24th December 2015) - Nesbitt, Eleanor
Abstract : Starting from recent UK media reports relating to Sikhs and vegetarianism, this article examines practice in the langar (gurdwaras' free food provision) before exploring earlier Sikh tradition (the scriptures, stories of the Gurus, and disciplinary codes) for religious guidance on meat-consumption. Contrary to some contemporary Sikh leaders' emphasis on vegetarianism, these older sources do not provide a consistently clear prohibition of meat-eating. Committed (Khalsa) Sikhs today belong to, or are at least influenced by, groupings such as the Akhand Kirtani Jatha and Damdami Taksal, each with its own code of practice. This article on the one hand suggests that Indic values and norms provide a relevant context to Sikh emphases on vegetarianism; on the other, it describes Sikhs' dismay that one of the UK's responses to meat provision in a religiously plural society directly conflicts with their code of conduct. The need for further ethnographic study is highlighted.